Reporting Vietnam (Library of America, 1998)
Volume 1 includes interviews and reportage by Neil Sheehan, David Halberstam, Russell Baker, Meg Greenfield, Martha Gellhorn, Ward Just, Tom Wolfe, Mary McCarthy, Seymour Hersh, Francine du Plessix and others. Volume 2 includes reportage by Seymour Hersh, Francine du Plessix Gray, John Saar, Gloria Emerson, Sydney Schanberg, Flora Lewis, Peter Arnett, and others.